Comparative evaluation of herbal gel as an adjunct to nonsurgical periodontal therapy in Stage III periodontitis: A randomized split-mouth clinical trial - Surekha Ramrao Rathod; Supriya Suresh Kaule; Pranjali Vijaykumar Bawankar; Abhay Pandurang Kolte (Journal of Indian Society of Periodontology)
Background and Objectives: Many Ayurvedic and herbal medications are used to overcome the drawbacks of allopathic medications. The objective of the current study was to assess and contrast the osteoanabolic effects of Picrorhiza kurroa and F. bengalensis gel on the quantity of bone fill in Stage III periodontitis using Radiovisiography (RVG). Materials and Methods: In the present split-mouth trial, 44 bilateral intrabony defects (IBDs) were randomly assigned to two groups. Group I received nonsurgical periodontal therapy (NSPT) alone, whereas Group II received NSPT along with Picrorhiza Kurroa and Ficus Bengalensis gel. The IBD fill using RVG was the primary outcome measurement and secondary outcomes were probing pocket depth, clinical attachment level, plaque index, and modified sulcus bleeding index reported at baseline, 3 months, and 6 months. Results: Both the study groups exhibited improvements in the measurements that were evaluated, although Group II significantly outperformed Group I in terms of IBD fill and clinical parameters. Conclusion: As a supplement to NSPT, the use of picrorhiza kurroa and ficus bengalensis gel is more advantageous in obtaining superior clinical and radiographic outcomes after 3 and 6 months.